A cláusula de declarações e garantias em contratos de compra e venda de participação societária - Schmitt, Marina Machado (2024)
This study aims to analyze the representations and warranties clause generally adopted in M&A contracts, purchase and sale of equity interest, investments or joint ventures, having its doctrinal as well as commercial aspect, analyzing the grounds for adding said clause and the functions on the contractual process of complex corporate operations. To do this, it begins with the study of the representations and warranties clause in its original environment, as well as the functions it performs. Afterwards, analyze the representations and warranties clause in relation to the national law, especially from the perspective of the general clause of good faith and the guarantee obligations. The application of legal institutes of civil law inherent to purchase and sale operations is also analyzed, such as consent defect, suspensive and resolutive conditions, object and legal defects, and failure to fulfill the obligation to deliver the good. Finally, after mapping the themes relevant to the matter and the comments on the doctrine, the way in which the Court of Justice of the State of São Paulo has faced the matter is analyzed, in order to observe the reception, or not, of the doctrinaires delineations by the court